Opportunities for Production and Utilization of Green Hydrogen in the Philippines - Collera, Angelie Azcuna; Agaton, Casper Boongaling (International Journal of Energy Economics and Policy, 2021)
The Philippines is exploring different alternative sources of energy to become energy-independent while significantly reducing the country's greenhouse gas emissions. Green hydrogen from renewable energy is one of the most sustainable alternatives with its application as an energy carrier and as a source of clean and sustainable energy as well as raw material for various industrial processes. As a preliminary study in the country, this paper aims to explore different production and utilization routes for a green hydrogen economy in the Philippines. Production from electrolysis includes various available renewable sources consisting of geothermal, hydropower, wind, solar, and biomass as well as ocean technology and nuclear energy when they become available in the future. Different utilization routes include the application of green hydrogen in the transportation, power generation, industry, and utility sectors. The results of this study can be incorporated in the development of the pathways for hydrogen economy in the Philippines and can be applied in other emerging economies. Keywords: green hydrogen, electrolysis, renewable energy, energy storage, sustainable energy JEL Classifications: O13, Q01, Q42, Q43, Q48 DOI: https://doi.org/10.32479/ijeep.11383